Complete genome sequence of Archaeoglobus profundus type strain (AV18T). Issue 3 (May 2010) - Jan, Mathias; Lapidus, Alla; Glavina Del Rio, Tijana; Copeland, Alex; Tice, Hope; Cheng, Jan-Fang; Lucas, Susan; Chen, Feng; Nolan, Matt; Goodwin, Lynne; Han, Cliff; Pitluck, Sam; et al.
Abstract Archaeoglobus profundus (Burggrafet al. 1990) is a hyperthermophilic archaeon in the euryarchaeal classArchaeoglobi, which is currently represented by the single familyArchaeoglobaceae, containing six validly named species and two strains ascribed to the genus 'Geoglobus ' which is taxonomically challenged as the corresponding type species has no validly published name. All members were isolated from marine hydrothermal habitats and are obligate anaerobes. Here we describe the features of the organism, together with the complete genome sequence and annotation. This is the second completed genome sequence of a member of the classArchaeoglobi . The 1, 563, 423 bp genome with its 1, 858 protein-coding and 52 RNA genes is a part of theG enomic E ncyclopedia of B acteria and A rchaea project.